Performance evaluation of uncoated carbide cutting tools in turning NST 37-2 steel. (2009)
In metal cutting operations, performance of the cutting tool is the major determinant of the productivity, functionality and production cost of the machined component. In this work, the performance of uncoated cemented carbide tools with International Standard Organisation (ISO) designation SNMA 120406 was evaluated for turning of NST 37.2 steel. Turning operations were conducted on M300 Harrison type lathe driven by 3.0 hp Kapak induction motor. The cutting conditions used were: cutting speed, 20.42, 29.06 and 42.42m/min; feed rate, 1.0, 1.8 and 2.2 mm/rev; and depth of cut, 0.2, 0.4 and 0.6 mm under dry machining. Results showed that both flank and nose wear increased with increase in number of pass, cutting speed, depth of cut and feed rate. The optical surface roughness of the machined workpiece varied from 0.658 - 0.924 and case hardening of the machined surface was observed. Segmented chips with smaller coil radii, which were less voluminous and more manageable were produced at all cutting conditions investigated. Chip breakability tends to increase with increase in cutting speed. The use of uncoated carbide tools has proved to enhance the productivity and surface quality in turning of NST 37-2 steel.